(untitled) (E Conference Zone, 2022)
In this article, we will gain knowledge about the emergence of phraseological units, their types of change, the explanation of their causes, the structural features of thematic phraseological units, as well as their use in modern English.At the same time, we can follow the research of researchers on phraseology in English.